Urbanization, land use change, and carbon emissions: Quantitative assessments for city-level carbon emissions in Beijing-Tianjin-Hebei region. (March 2021) - Zhou, Yuan; Chen, Mingxing; Tang, Zhipeng; Mei, Ziao
Highlights: City-level LUCEs in Beijing-Tianjin-Hebei region were calculated by coefficient correction. The relationship between urbanization and LUCEs was identified by EKC. Urban expansion and the increase of LUCEs were evident. Carbon emissions from built-up land accounted for the most of total emissions. Different urbanization level showed different time that LUCEs reach the peak. Abstract: Globally, urbanization has dramatically changed land cover, causing a rapid growth in carbon emissions and related risk of climate change. This study estimated city-level land use carbon emissions (LUCEs) using a novel method based on the correction coefficient calculated by the carbon emissions from energy consumption and basic land use emissions. The method was applied to 13 cities in the Beijing-Tianjin-Hebei (BTH) urban agglomeration in China using 30 m resolution land use data and energy balance tables (EBTs), and the Environmental Kuznets Curve (EKC) was used to discuss the relationship between urbanization and LUCEs in three typical models. The results revealed the expansion of built-up land in the BTH region, and LUCEs at the city-level increase continually, except in Beijing, which showed the most significant expansion of built-up land but a declining trend in LUCEs in recent years. The relationship between urbanization and LUCEs can be summarized into three modes: 'high urbanization - low emissions', 'middle urbanization - high emissions', and 'low urbanization - low emissions'. The results have great significance for the formulation of policies to reduce city-level carbon emission at different urbanization levels, and the implementation of high-quality people-oriented new-type urbanization can allow the realization of the carbon emission reduction targets of China.